2015
DOI: 10.1007/s00033-015-0493-2
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the normal component to the thermal resistance of turbulent liquid helium

Abstract: Previous results for the velocity profile of the normal component of helium II in counterflow are used to evaluate the viscous contribution to the effective thermal resistance.\ud It turns out that such a contribution becomes considerably higher than the usual Landau estimate, because in the presence of vortices the velocity profile is appreciably different\ud from the Poiseuille parabolic profile. Thus, a marked increase of the contribution of the normal component to the thermal resistance with respect to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The numerical studies of two-dimensional counterflow were performed [31], which differs from the 3D system. Saluto et al studied analytically the velocity profile of the normal fluid by using the one-fluid model [32,33], and found that the velocity profile could be flattened by superfluid turbulence.…”
mentioning
confidence: 99%
“…The numerical studies of two-dimensional counterflow were performed [31], which differs from the 3D system. Saluto et al studied analytically the velocity profile of the normal fluid by using the one-fluid model [32,33], and found that the velocity profile could be flattened by superfluid turbulence.…”
mentioning
confidence: 99%
“…[26] and [24] we have evaluated how much the presence of quantized vortices reduces the efficiency of the refrigeration by means of superfluid helium and in Refs. [27,28] how the profile of the heat flux (and the normal component) is modificed by their contribution. The continuity equation (2.1) has been written in terms of the specific volume V instead of the usual density ρ for future purposes.…”
Section: The Mathematical Modelmentioning
confidence: 99%